Simeon I the Great, the ruler of Bulgaria in the account of Leo the Deacon (Historia, VII, 7) - Leszka, Mirosław (Balcanica Posnaniensia. Acta et studia, 2020)
Simeon in the account of Leo the Deacon (Historia, VII, 7) is an unambiguously negative figure. A bold barbarian who dared not only to raid Byzantine territories, but also to demand that the Romans proclaim him a ruler. Even his victory at the Battle of Anchialos (917) was not the result of his military prowess, but a tear in the Byzantine camp. It should be clearly emphasized that he was not the hero of the aforementioned passage of Leo the Deacon's work, but Leo Phokas. The Bulgarian ruler was only a convenient tool in the hands of the Byzantine author for the purpose of showing a rather trivial truth that disagreement in one’s own camp and the desire for power lead to misfortunes, both for the individuals and for the nation.